BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN DIAKUINYA SESEORANG SEBAGAI PEMIMPIN OPINI DAN MANFAATNYA UNTUK KEGIATAN PENYULUHAN - Abdul Hanan; Ismail Pulungan; Richard W.E Lumintang (Jurnal Penyuluhan, 2005)
Opinion Leader at a certain areas, highly contributes to diffusion and adoption process, and has certain effect to social system whether the farmers rejected or accepted to a innovation. The research identified existence and function of Opinion Leader in an areas and analyzed correlated factors of recognition of Opinion Leader. Respondent were farmers of Floating Net Fish Culture at Coklat Area, Cirata Dam, District of Cianjur, West Java Province. The survey conducted since February until May 2005.The result showed that the farmers population, there were eight persons who considered by the respondents as sources of innovation and opinion. Futhermore internal characteristic had a positive value correlation among factors toward recognition level of Opinion Leader, but external characteristic showed negative correlation. Specially, the function of Opinion Leader those were strong correlation toward recognition farmers level to Opinion Leader.